Heads - Van Fleet, Matthew (New York : Simon & Schuster Books for Young Readers, 2010)
Rhyming text and animal illustrations with touchable textures, moving pages, and a final gatefold celebrate heads, the parts of which they are composed, and the ways that different creatures use them to sense the world around them.
Cover title.
"A Paula Wiseman book"--P. [4] of cover.
Keywords: Textured books -- Specimens; Lift-the-flap books -- Specimens; Animals -- Fiction; Head -- Fiction; Senses and sensation -- Fiction; Stories in rhyme; Textured books; Lift-the-flap books; Toy and movable books; Animals -- Fiction; Head -- Fiction; Senses and sensation -- Fiction; Toy and movable books; Stories in rhyme